Evolutionary Association of Stomatal Traits with Leaf Vein Density in Paphiopedilum, Orchidaceae - Zhang, Shi-Bao; Guan, Zhi-Jie; Sun, Mei; Zhang, Juan-Juan; Cao, Kun-Fang; Hu, Hong (PLOS ONE, 2012)
Background Both leaf attributes and stomatal traits are linked to water economy in land plants. However, it is unclear whether these two components are associated evolutionarily. Methodology/Principal Findings In characterizing the possible effect of phylogeny on leaf attributes and stomatal traits, we hypothesized that a correlated evolution exists between the two. Using a phylogenetic comparative method, we analyzed 14 leaf attributes and stomatal traits for 17 species in Paphiopedilum. Stomatal length (SL), stomatal area (SA), upper cuticular thickness (UCT), and total cuticular thickness (TCT) showed strong phylogenetic conservatism whereas stomatal density (SD) and stomatal index (SI) were significantly convergent. Leaf vein density was correlated with SL and SD whether or not phylogeny was considered. The lower epidermal thickness (LET) was correlated positively with SL, SA, and stomatal width but negatively with SD when phylogeny was not considered. When this phylogenetic influence was factored in, only the significant correlation between SL and LET remained. Conclusion/Significance Our results support the hypothesis for correlated evolution between stomatal traits and vein density in Paphiopedilum. However, they do not provide evidence for an evolutionary association between stomata and leaf thickness. These findings lend insight into the evolution of traits related to water economy for orchids under natural selection.